Postoperative Analgesic Effectiveness of Quadratus Lumborum Block for Cesarean Delivery under Spinal Anesthesia: A Systematic Review and Meta-analysis. (January 2021) - Hussain, Nasir; Brull, Richard; Weaver, Tristan; Zhou, Meiqin; Essandoh, Michael; Abdallah, Faraj W.
Abstract : Background: Spinal morphine is the mainstay of postcesarean analgesia. Quadratus lumborum block has recently been proposed as an adjunct or alternative to spinal morphine. The authors evaluated the analgesic effectiveness of quadratus lumborum block in cesarean delivery with and without spinal morphine. Methods: Randomized trials evaluating quadratus lumborum block benefits in elective cesarean delivery under spinal anesthesia were sought. Three comparisons were considered: spinal morphine versus spinal morphine and quadratus lumborum block; spinal morphine versus quadratus lumborum block; and no block or spinal morphine versus quadratus lumborum block. The two coprimary outcomes were postoperative (1) 24-h cumulative oral morphine equivalent consumption and (2) pain at 4 to 6 h. Secondary outcomes included area under the curve pain, time to analgesic request, block complications, and opioid-related side effects. Results: Twelve trials (924 patients) were analyzed. The mean differences (95% CIs) in 24-h morphine consumption and pain at 4 to 6 h for spinal morphine versus spinal morphine and quadratus lumborum block comparison were 0 mg (−2 to 1) and −0.1 cm (−0.7 to 0.4), respectively, indicating no benefit. For spinal morphine versus quadratus lumborum block, these differences were 7 mg (−2 to 15) and 0.6 cm (−0.7 to 1.8), respectively, also indicating no benefit. In contrast, for no block or spinal morphine versus quadratus lumborum block, improvements of −18 mg (−28 to −7) and −1.5 cm (−2.4 to −0.6) were observed, respectively, with quadratus lumborum block. Finally, for no block or spinal morphine versus quadratus lumborum block, quadratus lumborum block improved area under the 48-h pain curve by −4.4 cm · h (−5.0 to −3.8), exceeding the clinically important threshold (3.96 cm · h), but no differences were observed in the other comparisons. Conclusions: Moderate quality evidence suggests that quadratus lumborum block does not enhance analgesic outcomes when combined with or compared with spinal morphine. However, the block improves postcesarean analgesia in the absence of spinal morphine. The clinical utility of this block seems limited to situations in which spinal morphine is not used. Abstract : Quadratus lumborum block does not provide analgesic benefit when compared with or in addition to spinal morphine for postcesarean analgesia. In patients who do not receive spinal morphine, quadratus lumborum block does offer analgesic and opioid consumption benefit.Supplemental Digital Content is available in the text.